The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18805/ajdfr.dr-1612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Moringa oleifera Leaf Meal with Multienzyme on Performance, Carcass Characteristics and Economics of Production of Broiler Chicks

Abstract: Background: Moringa leaves have wide range of medicinal value including antimicrobial property. Therefore, it could be an alternative of antibiotic growth promoters in poultry but the presence of phytate and other anti-nutrients can reduce the bioavailability of certain nutrients. Enzymes may reduce anti-nutrients effect, break down non-starch polysaccharides (NSPs), reduce intestinal viscosity and ultimately improve digestibility of nutrients by improving gut performance. An experiment was conducted to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Carcass traits and meat quality are important indicators of animal health and breeding benefits, and diet composition and nutritional level are important factors (Meel et al, 2021;Sallam et al, 2021). Adding A. bisporus dry powder to broiler diets does not improve carcass traits (Kavyani et al, 2012), and the addition of F. velutipes residues to the diets of finishing pigs had no significant effect on their meat color .…”
Section: Can Improvementioning
confidence: 99%
“…Carcass traits and meat quality are important indicators of animal health and breeding benefits, and diet composition and nutritional level are important factors (Meel et al, 2021;Sallam et al, 2021). Adding A. bisporus dry powder to broiler diets does not improve carcass traits (Kavyani et al, 2012), and the addition of F. velutipes residues to the diets of finishing pigs had no significant effect on their meat color .…”
Section: Can Improvementioning
confidence: 99%
“…However, relatively higher edible and non-edible offal weights were observed with Moringa-based rations supplemented lambs (T2 and T3). This might be due to efficient digestion and absorption of nutrients leading to better growth and development of the gut (Meel, et al, 2021).…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…Comparison of prices of standard and experimental feed with the addition of enzymes and Selenium Meel et al (2021). andAmerah et al (2017) indicated that hyalase, protease and amylase enzymes (multienzymes) increased ADG and FCR in Ross (…”
mentioning
confidence: 99%